Biogenic α-Fe2O3Nanoparticles Enhance the Biological Activity of Trichoderma against the Plant Pathogen Sclerotinia sclerotiorum - Bilesky-José, Natalia; Maruyama, Cintia [UNESP]; Germano-Costa, Tais; Campos, Estefânia; Carvalho, Lucas [UNESP]; Grillo, Renato [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; De Lima, Renata (American Chemical Society (ACS), 2021)
The biogenic synthesis of metallic nanoparticles can contribute to resolving problems related to pests and soil fertilization. Among the different types of metallic nanoparticles, iron nanoparticles have shown good results, especially concerning toxicity because this metal is an essential micronutrient for all plants and can assist their growth, increasing the levels of carbohydrates, proteins, and chlorophyll. This work performed the green synthesis of biogenic iron oxide nanoparticles using the biological control agent Trichoderma harzianum as a stabilizing agent. The physicochemical properties of the nanoparticles were evaluated using the following techniques: dynamic light scattering, nanoparticle tracking analysis, scanning electron microscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. Cytotoxicity was evaluated using different cell lines, while comet and Allium cepa assays were used to assess genotoxicity. In addition, as a proof of concept, the biological activity of the nanoparticles against the pathogen Sclerotinia sclerotiorum (white mold) was evaluated using an in vitro antifungal activity test. The effect of the nanoparticles on seed germination was also evaluated. The results indicated that the nanoparticles consisted of hematite (α-Fe2O3) and had a mean size diameter of 207 ± 2 nm, polydispersity index of 0.45 ± 0.07, and zeta potential of 13 ± 2 mV. The biogenic iron oxide nanoparticles did not alter cell viability, compared to the controls, and did not lead to changes in the mitotic index, at the concentrations used. Furthermore, they were able to increase the proliferation of Trichoderma, which led to the inhibition of emergence of the pathogen S. sclerotiorum and did not affect the germination of the seeds. Therefore, the green synthesis of biogenic iron oxide nanoparticles based on T. harzianum is an attractive option for pest control, aiming at sustainable agricultural practices.
Keywords: agriculture; biogenic nanoparticles; Green synthesis; Trichoderma harzianum; α-Fe2O3nanoparticles